COMMUNITY DIASPORA IN THE MARITIM STRAIT OF MALAKA MALAYSIA : A CASE STUDY OF THE ACEH RUNCIT SHOP - Muhammad Ichsan (Aceh Anthropological Journal, 2020)
This journal article was written as a study of the Diaspora of the Aceh community in Malaysia. The Tsunami in Aceh 16 years ago has brought big changes to the people, both from the cultural aspects and new ideas that are constantly developing. The earthquake disaster followed by the tsunami caused damage and exacerbated political conflict between GAM and the TNI, which had a major impact on the Acehnese community. This condition made the people of Aceh start thinking about migrating to neighboring countries such as Malaysia because they saw more profitable opportunities. The Diaspora that occurred as a result of the Acehnese who migrated to Malaysia gave birth to a new culture. The presence of the Acehnese in Malaysia is marked by the formation of the Acehnese community and small shops which are the embodiment of the Aceh-Malaysia Diaspora. This study refers to ethnographic principles in the area of the village of Aceh, Yan Kedah. This research is a case study, an exploration and analysis technique in the investigation of a particular social unit. This research was conducted to determine the impact of the presence of the Acehnese diaspora on Malaysia. From the results of the discussion, it was found by researchers that the underlying reason for the Aceh and Malaysian Diaspora was due to the desire of the Acehnese people to leave the conflict zone which threatened the lives of the Acehnese community traders. Then the religious aspects also affect so that it is easy for the Acehnese people to adapt to Malaysia and be able to survive and unite the cultures of Aceh and Malaysia.